The influence of serotonin on the formation of clinical symptoms of functional gastrointestinal disorders in children - O.Yu. Belousova; Vaidotas Urbonas; L.V. Kazarian (Group of Companies Med Expert, LLC, 2023)
According to the Rome IV consensus (2016), functional gastrointestinal disorders (FGIDs) are disorders of the interaction between the gut and the brain. A crucial role in the realization of this mechanism is played by the key neurotransmitter serotonin. Aim - to investigate the influence of serotonin on the formation of clinical symptoms in children with FGIDs. Materials and methods. Under observation were 72 children aged 10-18 years with FGIDs. The Group I consisted of 30 children with combined functional dyspepsia (FD) and irritable bowel syndrome (IBS), the Group II included 42 children with FD. A control group of 20 healthy children was established. The diagnosis of FD and IBS was established based on the analysis of clinical symptoms according to the Rome IV criteria (2016). The severity of clinical symptoms was assessed using the Likert scale from 0 to 5 points. The study of serotonin content in whole blood was conducted using a fluorometric method after adsorption on carboxymethylcellulose. Results. The intensity of abdominal pain and the severity of dyspeptic syndrome in children with combined FD and IBS is higher than in children with FD (p<0.01; p<0.05, respectively). The serotonin content in whole blood in children with FGIDs is lower than in healthy children (p<0.001). In children with combined FD and IBS, the serotonin content is lower than in children with FD (p<0.05). Reverse correlation links were found between serotonin content and the intensity of pain syndrome (r=-0.7), the severity of dyspeptic syndromes (r=-0.5), constipation (r=-0.7), and diarrhea (r=0.7). Conclusions. The obtained research results indicate the influence of serotonin on the formation of clinical symptoms in children with FD and combined FD and IBS. The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee of the participating institution. The informed consent of the patient was obtained for conducting the studies. No conflict of interests was declared by the authors.